Distribution of Bexsero® antigen sequence types (BASTs) in invasive meningococcal disease isolates: implications for immunisation - Brehony, C; Rodrigues, C; Borrow, R; Smith, A; Cunney, R; Moxon, E; Martin C.J., M (Elsevier, 2016)
Serogroup B is the only major disease-associated capsular group of Neisseria meningitidis for which no protein-polysaccharide conjugate vaccine is available. This has led to the development of multi-component protein-based vaccines that target serogroup B invasive meningococcal disease (IMD), including Bexsero®, which was implemented for UK infants in 2015, and Trumenba®. Given the diversity of meningococcal protein antigens, post-implementation surveillance of IMD isolates, including characterisation of vaccine antigens, is essential for assessing the effectiveness of such vaccines. Whole genome sequencing (WGS), as realised in the Meningitis Research Foundation Meningococcus Genome Library (MRF-MGL), provides a rapid, comprehensive, and cost-effective approach to this. To facilitate the surveillance of the antigen targets included in Bexsero® (fHbp, PorA, NHBA and NadA) for protective immunity, a Bexsero® Antigen Sequence Type (BAST) scheme, based on deduced peptide sequence variants, was implemented in the PubMLST.org/neisseria database, which includes the MRF-MGL and other isolate collections. This scheme enabled the characterisation of vaccine antigen variants and here the invasive meningococci isolated in Great Britain and Ireland in the epidemiological years 2010/11 to 2013/14 are analysed. Many unique BASTs (647) were present, but nine of these accounted for 39% (775/1966) of isolates, with some temporal and geographic differences in BAST distribution. BASTs were strongly associated with other characteristics, such as serogroup and clonal complex (cc), and a significant increase in BAST-2 was associated with increased prevalence of serogroup W clonal complex 11 meningococci. Potential coverage was assessed by the examination of the antigen peptide sequences present in the vaccine and epidemiological dataset. There were 22.8-30.8% exact peptide matches to Bexsero® components and predicted coverage of 66.1%, based on genotype-phenotype modelling for 63.7% of serogroup B isolates from 2010/14 in UK and Ireland. While there are many caveats to this estimate, it lies within the range of other published estimates.